2012
DOI: 10.1074/jbc.m112.354548
|View full text |Cite
|
Sign up to set email alerts
|

Hindgut Innate Immunity and Regulation of Fecal Microbiota through Melanization in Insects

Abstract: Background: Many insects eat green leaves but excrete black feces using an unknown mechanism. Results: Hindgut cells produce prophenoloxidase and secrete it into the hindgut content. Conclusion: Prophenoloxidase induces the hindgut content and feces melanization by which bacteria flora are reduced. Significance: This is a first-time disclosure of the enigma of insect black feces and its biological significance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
95
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 105 publications
(104 citation statements)
references
References 30 publications
2
95
0
1
Order By: Relevance
“…Melanin generated from the precursors of dopa and dopamine by the activated phenol oxidases (POs) is important for immune responses [5, 79, 12, 1416, 19, 23, 24, 55, 56]. Genes ( TH , DDC etc . )…”
Section: Discussionmentioning
confidence: 99%
“…Melanin generated from the precursors of dopa and dopamine by the activated phenol oxidases (POs) is important for immune responses [5, 79, 12, 1416, 19, 23, 24, 55, 56]. Genes ( TH , DDC etc . )…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 15 μg total proteins were loaded for denaturing SDS-PAGE separation followed by Coomassie Brilliant Blue R-250 staining. Based on the molecular sizes of cuticle proteins listed in Additional file 2: Table S2, the gels that appeared to contain cuticle proteins were excised for LC-MS/MS assay as previously described [4]. The two databases used in this study were SilkDB (http://silkworm.genomics.org.cn/) and the B. mori protein sequence database which was downloaded from NCBI (www.ncbi.nlm.nih.gov) using the keyword “ Bombyx mori ”.…”
Section: Methodsmentioning
confidence: 99%
“…Food debris is then transferred to the hindgut for water, salt, and some nutrient absorption [3]. In herbivorous insects such Bombyx mori , prophenoloxidase (PPO) produced by hindgut epidermal cells eliminates the majority of microorganisms in the food debris by inducing melanization of feces, thus avoiding the distribution of potential pathogens into the surrounding habitat [4]. In the insect foregut, there is also PPO that can detoxify food phenolics [5].…”
Section: Introductionmentioning
confidence: 99%
“…Gut-associated bacteria can influence insect dietary preferences (4,19) and are reciprocally regulated by immune genes and enzymes of the hosts (20)(21)(22). Interestingly, microarray studies of RR-and WT-WCR adult heads have identified differentially expressed sequence tags showing sequence similarity with immune proteins (23).…”
mentioning
confidence: 99%